2019
DOI: 10.12659/msm.915518
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0002468 Regulates the Neuronal Differentiation of SH-SY5Y Cells by Modulating the MiR-561/E2F8 Axis

Abstract: Background It has been shown that circular RNAs (circRNAs) play a vital role in the regulation of neuronal differentiation; however, the precise role of circRNAs in human neuronal differentiation remains largely unexplored. Material/Methods A dual-luciferase reporter assay was carried out to confirm the targets of hsa_circ_0002468, miR-561, E2F8 (E2F transcription factor 8, a protein coding gene), and miR-561. We detected the expression of hsa_circ_0002468, miR-561, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Along with the development of gene sequencing, microarray, and genomics, an increasing number of circRNAs have been found to be involved in pathophysiological processes of the central nervous system, which also play an important role in the development of diseases in the central nervous system (D'Ambra, Capauto, & Morlando, 2019; He et al, 2019; Zhang, Yu, Bao, & Sun, 2019). Moreover, the abnormal expression of circRNAs may lead to a series of diseases of the central nervous system, which have a large effect on neuron cell differentiation (Yang, Xiang, et al, 2019). Currently, the important role of circRNAs in the pathological process of glioma is widely accepted (Nie, Li, Zhang, & Liu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the development of gene sequencing, microarray, and genomics, an increasing number of circRNAs have been found to be involved in pathophysiological processes of the central nervous system, which also play an important role in the development of diseases in the central nervous system (D'Ambra, Capauto, & Morlando, 2019; He et al, 2019; Zhang, Yu, Bao, & Sun, 2019). Moreover, the abnormal expression of circRNAs may lead to a series of diseases of the central nervous system, which have a large effect on neuron cell differentiation (Yang, Xiang, et al, 2019). Currently, the important role of circRNAs in the pathological process of glioma is widely accepted (Nie, Li, Zhang, & Liu, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To induce differentiation to neurons, SH-SY5Y cells are usually cultured in the presence of retinoic acid alone or combined with other chemicals or neurotrophic factors. [1][2][3][4][5][6] Neurotrophic factors, such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), play an important role in neuronal regeneration, but their clinical use is limited since they are not able to cross the blood brain barrier. 7 In the recent years, the synergy between nanotechnology and biomedicine in therapeutic and diagnostic tools has grown significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The circRNAs that are widely expressed in the mammalian brain (Rybak-Wolf et al, 2015 ; Hanan et al, 2017 ) have been suggested to participate in neurodevelopment (Hansen et al, 2013 ; Memczak et al, 2013 ), neuronal proliferation, and differentiation (Chen and Schuman, 2016 ; Yang et al, 2019 ; Suenkel et al, 2020 ). For example, a significant increase of certain circRNAs has been associated with myelination and neural maturation in the brain and spinal cord during postnatal development (Di Agostino et al, 2020 ), revealing the key role of circRNAs also in motoneuron development in cortex, brainstem, or spinal cord.…”
Section: Circrnas In Cnsmentioning
confidence: 99%
“…Another role of the circRNAs has been reported during development of the neocortex where they regulate spontaneous neuronal differentiation and are important to maintain the pool of cell progenitors (Suenkel et al, 2020 ). The spatiotemporal expression and function of lineage-specific circRNAs partly underlie the regulation of transcription factors to induce neuronal and glial differentiation and proliferation (Yang et al, 2019 ). Moreover, since circRNAs exhibit differential expression in different brain cells and areas, they could also represent a valuable tool for the development of novel targeted markers for gliomas progression and tumorigenicity (Sun et al, 2020 ).…”
Section: Circrnas In Cnsmentioning
confidence: 99%